A comparative U-Th-Pb (zircon-monazite) and 40Ar- 39Ar (muscovite-biotite) study of shear zones in northern Victoria Land (Antarctica): Implications for geochronology and localized reworking of the Ross Orogen - G. Di Vincenzo; R. Carosi; R. Palmeri; M. Tiepolo (Journal of Metamorphic Geology, 2007)
Mylonitic granites from two shear zones in northern Victoria Land (Antarctica) were investigated in order to examine the behaviour of the U-Th-Pb system in zircon and monazite and of the 40Ar- 39Ar system in micas during ductile deformation. Meso- and micro-structural data indicate that shear zones gently dip to the NE and SW, have an opposite sense of shear (top-to-the-SW and -NE, respectively) and developed under upper greenschist facies conditions. In situ U-Pb dating by laser-ablation inductively coupled plasma-mass spectrometry of zircon areas with well-preserved igneous zoning patterns (c. 490 Ma) confirm that granites were emplaced during the Early Cambrian to Early Ordovician Ross-Delamerian Orogeny. Monazite from the Bier Point Shear Zone (BPSZ) mainly yielded U-Th-Pb ages of c. 440 Ma, in agreement with in-situ Ar laserprobe ages of syn-shear muscovite and with most Ar ages of coexisting biotite. The agreement of ages derived from different decay schemes and from minerals with different crystal-chemical features suggests that isotope transport in the studied sample was mainly controlled by (re)crystallization processes and that the main episode of ductile deformation in the BPSZ occurred at c. 440 Ma. Cathodoluminscence imaging showed that zircon from the BPSZ contains decomposed areas with faint relics of oscillatory zoning. These areas yielded a U-Pb age pattern which mimics that of monazite but is slightly shifted towards older ages, supporting previous studies which suggest that 'ghost' structures may be affected by inheritance. In contrast, secondary structures in zircon from the Mt. Emison Shear Zone (MESZ) predominantly consist of overgrowths or totally recrystallized areas and gave U-Pb ages of c. 450 and 410 Ma. The c. 450-Ma date matches within errors most monazite U-Th-Pb ages and in-situ Ar ages on biotite aligned along the mylonitic foliation. This again suggests that isotope ages from the different minerals are (re)crystallization ages and constrains the time of shearing in the MESZ to ...